Understanding the impacts of lifestyle segmentation & perceived value on brand purchase intention: An empirical study in different product categories - Murat Akkaya (European Research on Management and Business Economics (ERMBE), 2021)
Several research attempts contributed to the literature related to lifestyle market segmentation mainly aimed to define lifestyle segments on a given product/service market in a positivist perspective. However, there is a lack of research interest on a normative perspective, questioning lifestyle segmentation effectiveness to have a guidance for brands regarding how it impacts brand purchase intention in different product types and consumer groups in comparison to brand perceived value. Therefore, this research purposes to define a formulation understanding the impact of lifestyle segmentation on purchase intention in relation to brand perceived value. After defining lifestyle segments of four different product category consumers using an AIO scale approach; the relationships through lifestyle, brand value perception and purchase intention were analysed empirically by using multiple analysis methods for selected product categories. As a result, the lifestyle segmentation couldn't be defined as the main and direct driver of brand purchase intention while consumer's perceived values which are affected by lifestyle significantly impact the purchase intention and this value mapping varies across product categories.
Keywords: 650; AIO; Lifestyle market segmentation; Perceived value; Purchase intention